Byron's daughter a biography of Elizabeth Medora Leigh - Turney, Catherine (Scribner, 1972)
Portrait of the life of the ill-starred Libby, said to have been born of Byron's incestuous affair with his half sister, Augusta.
Keywords: Byron, George Gordon Byron <Baron, 1788-1824> -- Family; Leigh, Elizabeth Medora <1814-1849>; Leigh, Elizabeth M. -- 1814-1849; Geschichte 1800-1900; Poets, English -- 19th century -- Family relationships; Biografie